Control of Membrane Surface Roughness and Pattern Wave Length by Changing the Nonsolvent (Water) Influx Rate - Khulbe, K.C.; Feng, C.Y.; Matsuura, T.; Lau, W.J.; Halakoo, E.; Gohari, R. Jamshidi; Ismail, A.F. (Journal of Membrane and Separation Technology, 2015)
The control of surface roughness of polyvinylidene fluoride (PVDF), polyethersulfone (PES), polysulfone (PS) and cellulose (CE) membranes was attempted by changing the rate of nonsolvent influx in the phase inversion process. PVDF and CE were chosen to represent membranes of high hydrophobicity and hydrophilicity, respectively, while PES and PS were chosen to represent membranes of intermediate hydrophobicity/-philicity. The concentration of sodium chloride (NaCl) in the aqueous coagulation medium was increased from 0 to 1.9 mol/L to decrease the rate of nonsolvent (water) influx in the solvent/nonsolvent exchange process. As well, the effect of polymer concentration and solvent on the surface roughness was investigated with respect to PVDF and PES. It was observed that the membrane surface roughness increased and decreased, respectively, for the hydrophobic PVDF and hydrophilic CE membrane as the rate of nonsolvent influx was decreased. For the PES and PS membranes of intermediate hydrophilic/-philicity, no significant roughness change was observed. The surface roughness tended to increase as the solution viscosity decreased. It was also observed that the pattern wave length of the hydrophobic membrane did not change significantly while that of the hydrophilic membrane increased significantly as the solvent influx rate was reduced. This trend is predictable by considering the shrinking or swelling of the cast polymer solution during the solvent/nonsolvent exchange process.